The Model Of Islamic Criminal Law Enforcement Against Cyber Crime: (An Integrative Analysis of the Maqāṣid al-Sharī‘ah Approach and Modern Cyber Law in Addressing the Challenges of Transnational Digital Crimes) - Achmad Kholiq; Akhmad Shodikin; Faishal Rahim (Ann Publisher, 2025)
Background. The advancement of digital technology has given rise to new forms of crimes known as cyber crimes, characterized by their transnational nature, rapid execution, and difficulty in being confined by state jurisdiction. Modern positive law has responded to this challenge through the formulation of cyber law, regulated at both national and international levels. In contrast, Islamic criminal law provides a normative framework derived from the concepts of jarīmah, ḥudūd, qiṣāṣ, and ta‘zīr. Aims. This article aims to analyze the model of Islamic criminal law enforcement against cybercrime and compare it with modern cyber law. Methods. The research employs a normative-comparative methodology, incorporating both conceptual and regulatory analysis. Result. The findings reveal that Islamic criminal law offers universal principles applicable to cybercrime through the category of ta‘zīr, which grants discretionary authority to the judge (qāḍī) in determining punishments based on public interest (maṣlaḥah). Meanwhile, modern cyber law emphasizes procedural aspects, digital evidence, and international mechanisms of enforcement. The comparative analysis indicates a convergence between the two systems in their objectives of protecting society, though they differ in terms of legitimacy sources and normative foundations. Conclusion. Hence, an integrative model of enforcement that combines the maqāṣid al-sharī‘ah with modern cyber law instruments could serve as a strategic alternative in addressing the complexity of cybercrime. Implication. Cybercrime law enforcement cannot rely on a single legal system. Instead, an integrative framework is needed to unite the strengths of Islamic criminal law and modern cyber law, thereby producing a more comprehensive, practical, and just cyber legal order in addressing the challenges of the digital age.